Bridging the Skills Gap: The Impact of High School CTE Programs on Local Industry Recruitment in Arizona - Ethan J. Miller; Aris Setiawan (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2026)
Arizona’s strategic sectors, particularly semiconductor manufacturing and healthcare, currently face an alarming skills gap as local talent availability fails to keep pace with rapid high-tech industrial expansion. This study explores the role of high school Career and Technical Education (CTE) programs in addressing this crisis through the Career and Technical Education Districts (CTED) model. Utilizing a qualitative descriptive case study approach, primary data were gathered through virtual interviews and in-depth document analysis of official reports from 2024–2025 to ensure research credibility despite remote implementation. The findings indicate that CTE concentrators achieve a graduation rate of 94.5%, with over 90% of graduates positively engaged in the economy. This high engagement is qualitatively driven by an industry-synchronized curriculum that mirrors actual workplace environments, fostering high student self-efficacy. Furthermore, the acquisition of industry-recognized credentials (IRC) emerged as a decisive factor that technically reduces recruitment costs and training time for local companies by providing instant proof of competence. The study concludes that while CTE programs serve as a strategic bridge, challenges regarding rural access and instructor shortages persist. To address the shortage of expert instructors, it is recommended that the state government simplify teaching certification pathways for industry practitioners through a specialized "adjunct instructor" scheme.